Bioactive Compounds in Barangan Banana Peel (Musa acuminata Colla.) as an Alternative for Antibacterial Drug Development - Razali, Mariany; Sembiring, Juhardi; Taufik, Muhammad (Universitas Syiah Kuala, 2023)
Barangan banana (Musa acuminata Colla.) is one of the banana varieties which is often found in Indonesia and is widely consumed so that banana peels become organic waste and need to be processed further. The novelty of this research is to prove the antibacterial activity of the ethanol extract contained in banana peels on the Pseudomonas aeruginosa bacteria which is supported by the GCMS instrument to show the active compounds contained which can be used in the development of anti-bacterial drugs. Pseudomonas aeruginosa is an opportunistic pathogen that is widespread and inhabits the homeland and environments in contact with humans and animals. These bacteria can attack infections of the skin, blood, lungs and digestive tract. The ethanol extract was tested against Pseudomonas aeruginosa using the agar well diffusion method. the compounds contained in the samples were analyzed using Phytochemical Test obtained alkaloids, flavonoid, terpenoids, steroids, saponins and tannins were obtained. There are six active compounds: Palmitinic acid (C16H32O2), Cyclopentanol acetate (C7H12O2), 1-(2-Thienyl) Ethanone oxime (C6H7NOS), 2-Furancarboxaldehyde (C5H4O2), 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl- (C6H8O4), and 2(3H)-Furanone, 5-methyl- (C5H6O2) with percent area respectively : 3,49, 12,60, 26,46, 20,85, 3,82, and 2,98 %. Antibacterial activity with inhibition zone diameters at concentrations of 100, 50, 25, and 12.5 mg/ml were 12.80, 10.70, 5.00 and 2.00 mm, respectively. This work will advance the development of antimicrobial drugs.